RETRACTED: Meningkatkan bonafiditas laporan keuangan UMKM scale up Tangerang Selatan melalui Sistem Informasi Aplikasi Pencatatan Informasi Keuangan (SI-APIK) - Aris Sanulika; Julian Maradina; Suciati Muanifah (Utan Kayu Publishing, 2020)
Retraction Notice Following a rigorous, carefully concerns and considered review of the article published in Journal of Indonesia Berdaya to article entitled “Meningkatkan Bonafiditas Laporan Keuangan UMKM Scale Up Tangerang Selatan Melalui Sistem Informasi Aplikasi Pencatatan Informasi Keuangan (SI-APIK)” Vol 1, No 2, pp. 61-67, July 2020, DOI: http://doi.org/10.47679/ib.202030This paper has been found to be in violation of the Journal of Indonesia Berdaya Publication principles and has been retracted (look at https://ukinstitute.org/journals/ib/about/editorialPolicies#custom-1).The article contained redundant material, the editor investigated and found that the paper published in Jurnal Lokabmas Kreatif : Loyalitas Kreatifitas Abdi Masyarakat Kreatif, Vol. 1, No. 2 (2020), pp. 5-10, entitled